Investigation on accuracy of sensor fusion for object detection of autonomous vehicle based on 2D Lidar and ultrasonic sensor - Mohammad Hazrul Ashraf, Rosdi; Ahmad Shahrizan, Abdul Ghani (Springer International Publishing, 2020)
This paper presents the investigation of sensor fusion between two types of sensors for object detection in order to be equipped in application of small autonomous vehicles. As mentioned in the previous researches, different types of sensors are often used to acquire information on the performance and detection accuracy as required in autonomous vehicle development. The technique that has been currently available for the purpose of obstacle detection is very costly. Thus, a new more cost-effective method is proposed in which the sensor can detect obstacle in the path. In addition, obstacle distance from the mobile robot or vehicle could also can be traced more accurate by using the sensor fusion